Uma nova interpretação da teoria do régio vicariato indiano - Arvizu, Fernando de (Revista da Faculdade de Direito da UFRGS, 2020)
RESUMO Este artigo discorre sobre o papel da teoria vicarialista no projeto de catequização levado a cabo nas Índias ao longo dos séculos XVI e XVII, além de informar a participação das monarquias católicas neste processo. O autor oferece uma visão sobre as questões políticas subjacentes ao desenrolar dessa teoria no período citado e, por fim, aponta para alguns dos seus impactos na América e na Europa, contrastada ao cenário das nascentes Igrejas Reformadas. PALAVRAS-CHAVE Teoria vicarialista. Patronato. Juan de Focher. Juan de Solórzano Pereira. ABSTRACT This article discusses the role of vicarial theory in the catechization project carried out in the Indies throughout the 16th and 17th centuries, appraising the participation of catholic monarchies in this process. The author offers an insight into the political issues underlying the development of this theory in the aforementioned period and, finally, points to some of its impacts in America and Europe, in contrast to the scenario of the dawning Reformed Churches. KEYWORDS Vicarial theory. Patronage. Juan de Focher. Juan de Solórzano Pereira. This article discusses the role of vicarial theory in the catechization project carried out in the Indies throughout the 16th and 17th centuries, appraising the participation of catholic monarchies in this process. The author offers an insight into the political issues underlying the development of this theory in the aforementioned period and, finally, points to some of its impacts in America and Europe, in contrast to the scenario of the dawning Reformed Churches..